Application of nanoparticles for asphaltenes adsorption and oxidation: A critical review of challenges and recent progress. (1st November 2020) - Sadegh Mazloom, Mohammad; Hemmati-Sarapardeh, Abdolhossein; Husein, Maen M.; Shokrollahzadeh Behbahani, Hassan; Zendehboudi, Sohrab
Highlights: An overview of NP use for asphaltenes adsorption and subsequent oxidation is provided. Most asphaltenes uptake is calculated based on UV–Vis measurements, which are not very reliable. Asphaltenes uptake by NPs increased with increasing asphaltenes aromaticity and polarity. Composite NPs are superior asphaltenes inhibitor relative to inorganic NPs. The rapid oxidation of adsorbed asphaltenes is a mass transfer enhancement effect. Abstract: Nanoparticles (NPs) have been recently recognized as effective asphaltenes adsorbents and deposition deterrents. The objective of this work is to provide a critical review and highlight the limitations of literature findings on NP use for asphaltenes adsorption and subsequent oxidation. Literature reports showed that asphaltenes uptake by NPs increases with increasing asphaltenes aromaticity and polarity. Moreover, NPs exhibit a higher selectivity to asphaltenes in the presence of other oil constituents such as resins. Composite NPs are superior asphaltenes deposition inhibitors owing to a synergy arising from attaching inorganic NPs to a hydrocarbon. It is worth noting that most of the asphaltenes uptake values were collected from model solutions, and were calculated based on UV–Vis measurements, which have been recently shown not to be very reliable. Acidic NPs and small size NPs are considered better asphaltenes adsorbents, whereas basic NPs and large size NPs are reported as better asphaltenes oxidation promoters. In situ combustion, which is an important enhanced oil recovery method, can be improved in the presence of NPs. Two mechanisms have been proposed to explain the rapid oxidation of adsorbed asphaltenes; namely mass transfer enhancement and catalytic effect. There is a stronger evidence in support of enhanced asphaltenes exposure to the mass of flowing air. Lastly, the impact of different reservoir conditions on asphaltenes adsorption is presented. The findings of this review improve our understanding of asphaltenes adsorption and the oxidation of adsorbed asphaltenes as well as the challenges hindering the effective use of NPs in asphaltenes related problems at both laboratory and field scales.